The power of information: a key component for the successful performance of Latvian social enterprises - Casno, Kristine; Skiltere, Daina; Sloka, Biruta (University of Latvia, 2020)
The purpose of the study is two-fold. First, the study aims to determine how informed consumers in Latvia are about social enterprises after a decade of discussion and activity within the field of social entrepreneurship which will later serve as a comparative reference base for following future developments and achievements in the field. Second, the study aims to investigate the relationship between the level of information consumers have about social enterprises and actual purchasing behavior of consumers in order to provide practical recommendations and suggestions for both social enterprise marketing specialists as well as government officials and organizations that support the field of social entrepreneurship in Latvia. Research methods applied: scientific publications analysis, legislative documents analysis, analysis of policy studies, as well as quantitative research method – survey of customers of social enterprise products and services. Many aspects are asked to evaluate in evaluation scale 1-10 to have opportunity for deeper analysis of views of respondents. Research results indicate that majority of consumers have average or below average information levels about social enterprises in Latvia which is still satisfactory given the young age of the field. Authors determine a statistically significant positive relationship between the informational level of consumers and their purchasing behavior which underscores the crucial importance of informative support needed by social enterprises. Authors also have determined the existence of an informational saturation point which indicates potentially higher economic returns from targeting consumers with rather low levels of information about social enterprises.
Keywords: social entrepreneurship; consumer behavior; social enterprise; consumer information level; Research Subject Categories::SOCIAL SCIENCES::Business and economics